Valorization of Paper Mill Sludge as Adsorbent in Adsorption Process of Copper (II) Ion from Synthetic Solution: Kinetic, Isotherm and Thermodynamic Studies - Yaras, Ali; Arslanoglu, Hasan (Springer Heidelberg, 2018)
This study investigates the process conditions of the adsorption of copper (II) ion onto paper mill sludge (PMS) in a batch process. These conditions are: concentration of initial solution, contact time, temperature and quantity of the adsorbent. Characteristic properties of PMS employed as an adsorbent in the experiments were defined using Fourier transform infrared spectroscopy (FT-IR) scanning electron microscopy (SEM) and elemental analyses. According to the obtained results, while the amount of removed copper (II) ion increased with an increase in the rate of the adsorbent and contact time, it decreased as a result of an increase in the temperature and initial solution concentration. Langmuir, Freundlich and Dubinin-Radushkevich (D-R) isotherms were implemented for the determination of the most appropriate isotherm model for the experimental data, and it was found that the process is in concordance with Langmuir equation. The maximum adsorption capacity of PMS was calculated as 114.42 mg g. In kinetic studies, the adsorption process of copper (II) ion onto PMS was controlled by the pseudo-second-order kinetic model. The calculated activation value ( was 38.61 kJ mol and demonstrates that the process occurred by physical adsorption mechanism. The values of the thermodynamic parameters such as enthalpy (, free energy () (-8.883 kJ mol) and entropy ( (0.101 kJ mol K) changes were determined to estimate the nature of the process. The results clearly showed that the process was of exothermic and spontaneous nature and that PMS could be utilized as an adsorbent for the removal of copper (II) ion from wastewater.
Keywords: Adsorption; Copper (II) ion; Isotherm; Kinetic; Thermodynamic; Paper mill sludge; Heavy metal